Mouse Control Using Head Movement - Ashtankar, Hemraj; Nagrale, Praful; Timande, Yogesh; Mandwi, Indu (Journal of Advance Research in Computer Science & Engineering (ISSN 2456-3552), 2015)
This system can be adapted accurately for detecting facial features. It is a free line up that allows you to control the pointer of the mouse on a processor with the help of head movements. The movements of head are liberated clicking with the help of mouse pointer abide over a spot on the screen. This is application which is helpful for the people who are disabled. The foremost spectators for this program are people who do not have committed control of a hand but who can only move their head. Citizens with, Spinal Cerebral Palsy, ALS (Amyotrophic lateral sclerosis), Muscular Atrophy, Traumatic Brain Injury, Multiple Sclerosis, various neurological disorders use this program and its predecessor to run all types of processor software.